Results of open prosthetics of abdominal aortic aneurysms using laparotomic and retroperitoneal approaches - S. E. Suzdaltsev; R. A. Sulimanov; K. M. Vakhitov; S. I. Sukovatkin; I. V. Korotkov; O. Yu. Kalyuzhnaya; T. M. Gasainiev; M. D. Grigoryan; A. D. Kitsalmagomedova (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to evaluate the results of surgical treatment of abdominal aortic aneurysm using laparotomic and retroperitoneal approaches.METHODS AND MATERIALS. The study included 206 patients operated on at the Department of Vascular Surgery of the Novgorod Regional Clinical Hospital from 2010 to 2018. All patients were divided into 2 groups. The first – 112 people, whose surgical intervention was performed through laparotomic approach. The second – 94 patients, approach to the aorta was made by the retroperitoneal technique according to Rob. comparison of non-specific life-threatening complications included the development of myocardial infarction and acute cardiovascular failure, acute respiratory distress syndrome and respiratory failure, the development of ischemic colitis and small bowel obstruction, which required repeated interventions. The development of acute renal injury was characterized as an increase in creatinine by 50 % from baseline or a decrease in glomerular filtration rate (GFR) by more than 25 %. This group of complications also included ischemic stroke, sepsis, and multiple organ failure. Wound complications included insolvency of postoperative wounds of retroperitoneal and laparotomic approaches, cases of eventration.RESULTS. When analyzing the incidence of nonspecific complications, it was found that in group I their frequency was 41 (46.6 %) clinical cases, and in group II – 26 (27.6 %) (p=0.173*). In group I, the incidence of cardiovascular complications significantly exceeded those in group II – 17 (15.2 %) vs 6 (6.4 %) (p*=0.046). The incidence of gastrointestinal complications was also significantly higher in group I – 9 (8 %) vs 1 (1.06 %) (p*=0.021). The frequency of deaths in groups I and II did not differ significantly in 7 (6.25 %) and 5 (5.3 %) cases (p*=0.77).CONCLUSION. As our study showed, retroperitoneal approach is a worthy alternative to laparotomy, mainly in case of repeated interventions, as well as in the presence of signs of visceral obesity of the patient. At the same time, laparotomic approach is associated with a higher risk of developing cardiovascular and gastrointestinal complications in the treatment of abdominal aortic aneurysms.